Design of Effective Cryopreservation Conditions for Candida Yeast-Like Fungi - Vysekantsev, I. P.; Martsenyuk, V. F.; Sirenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2008)
The influences of freezing rates over 0.25–100°C/min range and DMSO, glycerol and ethanol cryoprotectants on the viability of yeast-like fungi C.albicans ATCC885 were studied. It has been shown that maximum level of survival of yeast-like fungi was provided by freezing rates over 3.5–10°C/min range in beer wort and adding of 5% DMSO or 5% glycerol.